ANALISIS MOTIVASI BELAJAR PADA SISWA ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) DI SD NEGERI 023 SAMARINDA UTARA - Salim, Nur Agus; Aslindah, Andi; Handayani, Eka Selvi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This study intended to determine the background of learning motivation of ADHD (Attention Deficit Hyperactivity Disorder) students. Besides knowing how to handle ADHD students and whatever factors that influence learning motivation. This was a qualitative descriptive study and the research subjects comprised 5 ADHD students, parents and homeroom teachers. The research instrument used observation sheets, interview sheets, and cameras. Data analysis technique was done by obtaining data from the field going to observation, interviews, and documentation, data reduction, data presentation then drawing conclusions. The sampling technique uses snowball sampling techniques and uses source triangulation and triangulation techniques. The results showed that the background of ADHD students' learning motivation tends to be minimal compared to students. Due to the condition of ADHD students have three symptoms, hyperactivity, intention and impulsivity. With this symptom condition, ADHD students must get a special approach such as more attention and be able to handle it without taking rough actions or punishing because it can affect the mental condition in ADHD students.